Time-dependent settlement analysis of a geosynthetic-reinforced soil. Issue 2 (April 2003) - Shukla, S. K.; Yin, J. H.
Abstract : This paper presents a mechanical modelling approach to determining the settlement of a geosynthetic-reinforced engineered granular fill–saturated soft foundation soil system. In this approach, the geosynthetic-reinforced engineered granular fill is represented by a reinforced Timoshenko beam and the saturated soft foundation soil is idealised as a Terzaghi spring–dashpot system. A parametric study has been carried out to observe the settlement response of the reinforced soil system along with the tension in the geosynthetic reinforcement at different stages of consolidation of the saturated soil.